Gender differences in susceptibility to schizophrenia: Potential implication of neurosteroids. (October 2017) - Huang, Yu-Chi; Hung, Chi-Fa; Lin, Pao-Yen; Lee, Yu; Wu, Chih-Ching; Hsu, Su-Ting; Chen, Chien-Chih; Chong, Mian-Yoon; Lin, Chieh-Hsin; Wang, Liang-Jen
Highlights: Compared to healthy males, males with schizophrenia had significantly lower serum levels of DHEA and pregnenolone. In males with schizophrenia, serum levels of DHEA and DHEA-S were associated with the age of onset and duration of illness. In males with schizophrenia, pregnenolone levels were associated with general symptoms of the PANSS. In females, neurosteroid levels were not associated with schizophrenia psychopathology. Neurosteroids may be involved in the gender differences found in the susceptibility to schizophrenia. Abstract: Past research has indicated gender differences in the clinical characteristics and course of schizophrenia. In this study, we investigated whether gender differences in the manifestation of schizophrenia are correlated with neurosteroids, including dehydroepiandrosterone (DHEA), dehydroepiandrosterone sulfate (DHEA-S), and pregnenolone. We further explored the potential relationship between the aforementioned neurosteroids and psychopathology. We recruited 65 schizophrenic patients (36 males and 29 females) and 103 healthy control subjects (47 males and 56 females) and obtained blood samples from the subjects in the morning while in a fasting state to determine the serum levels of DHEA, DHEA-S, and pregnenolone. The psychopathology and mood symptoms of patients with schizophrenia were evaluated using the Positive and Negative Syndrome Scale (PANSS) and 17-item Hamilton Depression Rating Scale, respectively. Compared to the male control subjects, male patients with schizophrenia had significantly lower serum levels of DHEA and pregnenolone. In males with schizophrenia, the serum levels of DHEA and DHEA-S were associated with the age of onset and the duration of illness, while pregnenolone levels were associated with general symptoms of the PANSS. However, none of the neurosteroid levels were different between the female patients with schizophrenia and the female controls, and no significant correlation between neurosteroid levels and psychopathology evaluations was found among the schizophrenic females. Neurosteroids, including DHEA, DHEA-S, and pregnenolone, are involved in the pathophysiology of schizophrenia in male patients, but not in female ones. Therefore, our findings suggest that neurosteroids may be associated with gender differences in susceptibility to schizophrenia.